6-2(4x)+7=0

Simple and best practice solution for 6-2(4x)+7=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-2(4x)+7=0 equation:


Simplifying
6 + -2(4x) + 7 = 0

Remove parenthesis around (4x)
6 + -2 * 4x + 7 = 0

Multiply -2 * 4
6 + -8x + 7 = 0

Reorder the terms:
6 + 7 + -8x = 0

Combine like terms: 6 + 7 = 13
13 + -8x = 0

Solving
13 + -8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + -8x = 0 + -13

Combine like terms: 13 + -13 = 0
0 + -8x = 0 + -13
-8x = 0 + -13

Combine like terms: 0 + -13 = -13
-8x = -13

Divide each side by '-8'.
x = 1.625

Simplifying
x = 1.625

See similar equations:

| 5(-2)=y+6 | | 7a*3a= | | 5(0)=y+6 | | 4-9p=49 | | 3/4+5/3 | | 5(2)=y+6 | | 9*n=53 | | 2y-6.2+y=8.8 | | -4+8X=5+2X | | 2(m+5)=28 | | 12+(21-6)/3 | | (4y+3)-(-3y-6)=-2 | | -2(6)+9=-(9)-3 | | -2(-12)+9=-(0)-3 | | 4(x-6)+2=6x-6 | | 5x-1+-2x+7=9 | | 65-98+(85-6x)=9 | | (9x^3-4x^2+3x)-(7x^2+2x+4)= | | 3x/4-21x/32=9/8 | | 12.4=9+t | | -2(2)+9=-(-4)-3 | | 4(y-1/2)=y-6(5-Y) | | 3x/4-21x/32=-11/8 | | 4=-5/x-6 | | 10x+28=4x+178 | | (9b-5)-4(2b+2)=-3 | | 4x-8=-11 | | -5(3)+15=-10(3) | | 5z+5=5z+5 | | 185-6x=30x+17 | | -5(-1)+15=-10(1) | | 9+2z-8=9z+3-5z |

Equations solver categories